Restore our indian traditional snacks among School going children - S.VIJAYALAKSHMI; T.KANCHANA; S.VASANTHA; N.DEVI; A.ARUN (International Journal of Pharma and Bio Sciences, 2016)
Snacks are considered as dietary supplements for many children who are affected with nutritional related disorders. Hence, the aim of this study was to monitor the snacks pattern of school going children during their break-time. This study was also proposed to provide them with the Indian traditional snacks and find the preferences of those snacks among the school going children. Case study was the most appropriate tool to find out the restoration of Indian traditional snacks among school going children and statistical calculation was carried out. Overall results from this study have shown that the Cookies / Cakes/ wafers were consumed by most of the school children during their break-time. On the contrary a vast percentage of the school children preferred our Indian traditional snacks. This study concludes that their parents are in urge to restore our Indian traditional snacks among the children.